The altitude project: An international collaborative research project on altitude training in elite swimmers - Rodriguez, F. A.; Levine, B. D. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: : Altitude training (AT) is a common practice among swimmers although scientific evidence of its benefits is scarce and controversial, particularly in elite athletes. The Altitude Project aims to: 1) determine the effectiveness of AT using the Hi-Hi (living and training at moderate altitude), or the Hi-Lo (high intensity training performed at lower altitude) models, in comparison with sea level training; 2) establish the physiological mechanisms involved; 3) ascertain whether altitude training affects swimming technique; 4) uncover any negative impact on athletes` health and performance; and 5) identify markers of individual response and adaptation to AT. METHODS: An international group of researchers belonging to universities and sports organizations of different nations, supported by the IOC and FINA among others, will develop a major international study starting at October, 2010. About 40 male and female elite swimmers from various countries and their coaches will participate in a controlled, matchedpaired, balanced experiment with three interventions: Hi-Hi (2320 m), Hi-Lo (high intensity training at 690 m, Granada), and Lo-Lo (sea level, Barcelona). After the first set of tests, subjects will be tched by gender, competitive level, and VO2max, and to one of the three groups. Initial and repeated measurements along the study will include: 1) performance testing, 2) swimming economy and metabolic testing (including VO2max and MAOD), 3) swimming technique and kinematics, 4) hematology (including flux cytometry and total Hb mass), 5) prooxidant/ antioxidant balance, 6) immunological status, 7) heart rate and arterial blood pressure variability, 8) echocardiography, and 9) clinical